Intermodal transportation of modular structure units. Issue 2 (2018) - Liu, Zhiyuan; Gu, Ziyuan; Bai, Yu; Zhong, Ning
With the rapid development of international cooperation in the construction industry, modular construction has been widely promoted in recent years especially for apartments, social housing and schools. This paper aims to address the intermodal transportation plan for modular structure units (MSUs). An overview of MSUs is provided followed by a discussion on different transportation modes. To prevent damages to modules, containers are typically used for maritime shipping. Comparative results show that the 12.1 m (40 ft) hicube container is most suited for transporting MSUs. With containerisation, an optimal urban transportation plan is proposed consisting of four major steps: identifying the feasible transportation network, establishing the transport cost function, solving the K-shortest paths problem, and assigning MSUs using the logit model.